2016
DOI: 10.3109/13561820.2016.1173656
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual review of interprofessional expertise in child safeguarding

Abstract: It is increasingly accepted that practitioners across a range of professional fields must work together in order to promote children's welfare and protect them from harm. However, it has also become apparent that interprofessional working is a challenging area of practice that cannot simply be prescribed through protocols and procedures, nor acquired as a set of technical competences. This paper develops the concept of interprofessional expertise in order to explain how practitioners become more proficient at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Whereas competencies measure performance of a task, curriculum that develops capability may be conceived as extending learning to build individuals’ ability to adapt and generate new ideas to improve performance [ 22 ]. It has been suggested that ‘interprofessionality’ itself may be a core capability linking IPL and subsequent interprofessional collaborative practice [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas competencies measure performance of a task, curriculum that develops capability may be conceived as extending learning to build individuals’ ability to adapt and generate new ideas to improve performance [ 22 ]. It has been suggested that ‘interprofessionality’ itself may be a core capability linking IPL and subsequent interprofessional collaborative practice [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nagy Britanniában a kétezres évek elején a gyermekvédelmi törvényben történt változások okán az új törvényi iránymutatások megkövetelik a szakemberektől, hogy alkossanak egy csapatot a gyermekek körül a gyermekvédelmi tervek végrehajtása és a legkiszolgáltatottabb gyermekek szükségleteinek kielégítése érdekében. (Hood, Gillespie, Davies, 2016) A közösségi tevékenységek közül az Egyesült Királyságban dolgozó szakemberek válaszaiból kitűnik az interprofesszionális team-ben való működés gyakorisága is az oktatási intézményben. Mindenki egyetértett abban, hogy ez egy nagyon fontos része az iskolai szociális munkás feladatkörének.…”
Section: Csoportos Tevékenységunclassified
“…Good communication ensures positive collaboration between MAPs, which is vital to meet the safeguarding needs of vulnerable children (HM Government, 2018; Horwath & Morrison, 2011). However, the challenges of interprofessional working when safeguarding children have been consistently highlighted in the literature (Doyle, 2008; Horwath & Morrison, 2011; Hood et al, 2016; Machura, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recurrent theme to emerge from the reviews is a need for improved collaboration between local authorities (also known as town councils or boroughs) and healthcare professionals (Children's and Family Bill,). While acknowledging that the complexity of child protection cases can affect communication, information sharing, and understanding between multidisciplinary teams, Hood et al (2016) assert that more work needs to be done to learn the lessons from case reviews and put their resulting recommendations into practice.…”
mentioning
confidence: 99%